A 3d monofilament biosuture for microvascular surgery applications - de la Harpe, Kara Mia (My University, 2022)
With a huge global market of over $ 3.7 billion annually and employment in more than 12 million procedures per year, sutures are one of the most widely used medical devices of the day. Yet, the ideal suture material does not exist, and surgeons battle on a daily basis with the various complications caused by these key medical devices. The ideal suture should create an environment that not only supports, but also encourages wound healing by delicately approximating the wound edges without contributing to the damage and inflammatory activity of the wound. Regrettably, most suture materials have no inherent therapeutic activity and contrarily cause damage to the tissue through effects such as ‘sawing’ and ‘cheese-wiring’, that can delay the wound healing process. Hence, there is an urgent need for a more advanced suture material that is, not only biocompatible and safe, but also inherently bioactive and able to either prevent complications or contribute to the wound healing process. The aim of this study is to design, fabricate and evaluate a novel absorbable, monofilament biosuture material, that consist only of natural biopolymers with established biocompatibility and biodegradability. The biosuture will be transformed into a drug delivery device, that can provide localized, sustained drug release to help address complications such as ischemic reperfusion injury and the dreaded ‘no-reflow’ phenomenon during microvascular surgery. Various biopolymers, such as alginate, pectin, nanocellulose and gelatin, were investigated during the preliminary design phase, to obtain an optimized biosuture formulation that could meet the United Stated Pharmacopoeia’s requirements for suture tensile strength. The optimized formulation consisted of alginate (6% w/v), pectin (0.1% w/v), gelatin (3% w/v) and glycerol (4% v/v). Different methods of drug loading were also investigated and the optimal method, namely a lipid-drug coating, selected for further characterization. The biosutures displayed excellent mechanical properties with a maximum load failure of 4.14 N in the straight configuration. SEM images revealed a smooth surface morphology and even coating of the biosuture with the lipid-drug layer. The lipid-drug coating displayed a suitable loading capacity (53 – 101 ug/cm) and provided controlled drug release over a period of seven days. The biosutures degraded by means of surface erosion and were fully eroded after 5 weeks of incubation. The physiochemical and thermal properties of the biosutures were investigated by means of FTIR, XRD, TGA and DSC) and showed favourable results. The biosutures also displayed excellent biocompatibility and improved cell viability over a period of 48 hours. The biosutures displayed good hemocompatibility with no haemolytic or platelet activating abilities. The results are very encouraging warrant further in vivo investigation of the newly developed biosuture material.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Pharmacy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022